﻿Complementary and alternatives care for postpartum preeclampsia: A scoping review - Susilo Rini; Soetrisno Soetrisno; Tri Rejeki Andayani; Suminah Suminah (Pensoft Publishers, 2023)
This scoping review aimed to examine the existing evidence on complementary and alternative medicine interventions for preeclampsia, emphasizing empowering midwives in postpartum treatment. Three databases (PubMed, Web of Science, Scopus) were used following the PRISMA-2020 guidelines to find articles from January 2012 to December 2022 and synthesized using Rayyan AI software. A total of 707 articles were initially identified, 7 were included in the review. Traditional Chinese Medicine combined with Western medicine showed promise in treating severe preeclampsia. Massage therapy reduced anxiety, aromatherapy positively affected postpartum well-being, and warm foot therapy reduced swelling associated with postpartum preeclampsia. Using herbal ingredients, lavender aromatherapy, magnesium sulfate, massage, and physical therapy contributed to successful postpartum preeclampsia management. Complementary and alternative medicine, collaboration with community health workers, clear guidelines, targeted training, and future research are crucial for effective postpartum preeclampsia management.